AB0528 Bone mineral density, vertebral fractures and their determinants in ankylosing spondylitis. (23rd January 2014) - Rossini, M.; Mahamid, H.; Caimmi, C.; Orsolini, G.; Povino, M. R.; Gatti, D.; Viapiana, O.; Fracassi, E.; Carletto, A.; Biondan, M.; Adami, S.
Abstract : Background: Osteoporosis responsible for loss of bone strength and vertebral fracture (VF) rates ranged from 0% to 18% have been reported in patients with ankylosing spondylitis (AS). Objectives: In this study we examined the prevalence of low bone mineral density (BMD) and VF in patients with AS (modified New York criteria), and investigated the associations between BMD or VF and demographic, body composition or disease-related parameters. Methods: Skeletal and body composition assessment included dual X-ray Absortiometry (DXA) at the lumbar spine, hip and total body and radiographs of the spine. The presence of VF was established by the Genant's semi-quantitative method. Results: A total of 79 AS patients, 65 males and 14 females with mean age of 43 and 49 years, respectively and with a mean disease duration of 10 years were included. Mean Z score BMD (SD below the age- and gender-matched mean reference value) were slightly decreased only in male patients, both at lumbar spine and total hip (-0, 4 p=0, 05; -0, 3 p<0, 01), while mean total body Z score BMD were positive in both genders (female +1, 2 p<0, 05; male +0, 7 p<0, 001), independent of the presence of syndesmophytes. Z score BMD values at both total hip and lumbar spine were directly and significantly (p<0.01) associated with body mass index (BMI, Kg/m 2 ); Z score BMD were significantly correlated with both fat and lean mass (kg), measured by DXA, only at hip sites. Z score BMD were significantly lower in the 36 patients with syndesmophytes and in those (19%) with peripheral joints involvement. Despite reasonably preserved BMD values at least one VF was identified in 31% of males and 14% of females; most VF were located at thoracic-lumbar transition and were mild wedge fractures. The presence of VF was not associated with BMD values (ANOVA) but rather with peripheral joints involvement (chi-square test, p<0.01), Bath Ankylosing Spondylitis Metrology Index (logistic regression, p<0, 01), and Bath Ankylosing Spondylitis Functional Index (p<0, 01). Conclusions: In this study we found that BMD is relatively well preserved in AS patients. The total body BMD values above the normal range suggest that the overall bone formation might be somewhat increased despite the propensity to decreased mobility. VF are very common particularly in male AS patients: its occurrence is unrelated with BMD values while it is significantly correlated with clinical parameters of disease activity and functional impairment. Disclosure of Interest: None Declared